(untitled) (Indian Journal of Child Health, 2024)
Objectives: The objective of this study was to determine the neurodevelopmental status of pre-term babies between <34 weeks of gestation and equal to or more than 25 weeks of gestation, at corrected 2 years of age with respect to their antenatal steroid status. Materials and Methods: This population-level prospective study was conducted over a period of 6 years from 2017 to 2023 in middle Kerala. Pre-term babies with gestational age at birth between <34 weeks and equal to or more than 25 completed weeks, presenting for follow-up within 3 months of delivery, were randomly enrolled for the study. A total of 150 children were followed up and neurodevelopmental assessment done using Bayley Scales of Infant and Toddler Development edition-3 at their corrected 2 years of age. Approval for this prospective observational study was obtained from the Institutional Ethics Committee, School of Behavioral Sciences, Mahatma Gandhi University, Kottayam, Kerala, dated September 22, 2017. Results: Eighty-one pre-term <34 weeks babies belonged to the antenatal steroid complete group, 40 pre-term <34 weeks babies belonged to the antenatal steroid partial group, and 29 pre-term <34 weeks babies belonged to the nil steroid group. Total neurodevelopmental status score and domain-wise, cognitive, language, motor, and social-emotional developmental scores show significantly higher scores for pre-term <34 weeks with antenatal history of complete course steroid administered before pre-term delivery compared to partial and nil antenatal steroid group. Conclusions: Antenatal steroids are having a significant impact on the overall neurodevelopmental outcome of pre-term babies equal to or more than 25 weeks of gestation and <34 weeks of gestation, at their corrected 2 years of age, the maximum benefit for complete antenatal steroid group pre-term babies, equal to or more than 25 weeks and <34 completed weeks of gestation when compared with pre-term babies, equal to or more than 25 weeks and <34 completed weeks of gestation without any antenatal steroids.